Desarrollo de indicadores de sostenibilidad ambiental en el páramo de Aluchán ubicado en la parroquia Cusubamba, cantón Salcedo, provincia de Cotopaxi, 2022. - Salguero Zambonino, Lisbeth Yadira (2022)
This project refers to the selection and development of environmental sustainability indicators in the Aluchán Highland through the characterization of the area allows contextualizing environmental variables related to anthropic activities in a continuously degraded ecosystem, For which it is important to establish control and development strategies that through the ordinance of the Municipal Government of Salcedo can conserve and protect the biodiversity of the Highland, the deductive method was used through the execution of research ideas in a specific way, also determining the inductive method that allowed observing and analyzing the data collected from anthropic activities that cause the problems in the Aluchán Highland. The PER model also helped to describe the human actions and activities carried out in the Highland (Pressure), verifying the current situation of the natural resources and the environment (State) and thus being able to establish solutions to address the problem (Response). In order to respond to the research topic, an in-situ visit was carried out where the problems caused by anthropic activities in the Highland such as agriculture, cattle raising and tourism were evidenced through the application of techniques such as interviews and surveys that were filled out by 90 heads of household, 85. 6% accepted the proposal for the implementation of environmental sustainability indicators in the Aluchán Highland which leads to the establishment of strategies to achieve the ecosystemic balance of the area by analyzing the environmental, economic and social impacts where it is estimated to contribute as part of a sustainability approach to the planning and implementation of future activities, providing solutions to the environmental problems identified in the Highland.